Transcutaneous hitching sutures in paediatric minimally invasive surgery: A novel technique of "assistant without port" - Sanat Kumar Khanna; Kamal Kishore; Gaurav Panchal (Wolters Kluwer Medknow Publications, 2024)
Background: Transcutaneous hitching sutures in paediatric minimally invasive surgery (MIS) is a unique and rare technique. This technique has been used previously in adult patients undergoing gastric resections and laparoscopic cholecystectomy; however, its use in paediatric population has never been reported in the world literature. The primary objective of this study was to bring out the advantages and feasibility of this technique in minimally invasive gastrointestinal, hepatobiliary, urological and thoracoscopic surgeries on paediatric patients. Materials and Methods: This retrospective observational study was conducted on 167 paediatric patients who underwent MIS surgery for different indications between April 2016 and March 2020 at two paediatric surgery tertiary care centres. Results: A total of 167 patients, including 91 boys and 76 girl patients between the age group of new-born period to 12 years were operated. The mean hospital stay was 4 days. Five out of 167 cases (3%) had post-operative surgical emphysema, which resolved spontaneously. At 6-month follow-up, parental satisfaction was 100%, and in 99% of patients, scars were imperceptible. Conclusion: This versatile technique is of exemplary utility, especially in paediatric patients where there is a paucity of working space at low intra-abdominal pressure, and eases the dissection even in narrow and closed spaces with a better functional and cosmetic outcome.